PEMIKIRAN KEAGAMAAN RAJA ALI HAJI - Alimuddin Hassan (Sosial Budaya, 2015)
This article aims to describe aspects of intellectual of Raja Ali Haji. Hel well known as the exposure was so much to say perfect. From the aspects of intellectual Raja Ali Haji seen in his writings, presumably Raja Ali Haji agree with the opinion of Imam Ghazali about the power of the pen, namely that "the pen is mightier than the thousand of sword" .